A demissão do outro na esquizofrenia : o dito esquizofrênico sem a ajuda de nenhum discurso estabelecido - Ana Luíza Mota San'tanna (2016)
The dismissal of the Other is the object that permeates this entire work. Starting from the clinic case report, we found out that the way that the patient behaved was related to the dismissal of the Other and it repeated in all of her “relationships”. So, we intended to define the dismissal of the Other’s statute. Using the clinic case as a instrument to insert a focus in the theory, we searched for elements the could help us to do that, and our guide was the lacanian psychoanalysis. We discovered that the concept of discourse could help us to understand the relationship between the subject and the Other. And we also discovered that the lacanian characterization of the schizophrenic subject could help us to explain the patient behavior. The research’s results indicated that the dismissal of the Other has multiple causes, but it seems to happen only in cases of schizophrenia. The analysis of the psychosis’s irruption – that created a possibility to develop the idea of a misery-promise – worked out as a research field for new opportunities of investigation about this theme.